Impact of Social Media on Adolescent Social Interaction Patterns in Digital Education - Kafina Agni Fitrati; Rehany Saleha (Yayasan Cerdas Pedia Indonesia, 2025)
This research analyzes the impact of social media on adolescent social interaction patterns within Indonesia’s digital education landscape. Utilizing a qualitative systematic literature review guided by Media Ecology and Social Capital theories, the study examines how platforms like TikTok and Instagram reshape social dynamics. Findings indicate that while digital connectivity expands bridging social capital through diverse global networks, it simultaneously erodes bonding capital and face-to-face communication quality. The emergence of a pervasive